Distinct oligodendrocyte populations have spatial preference and different responses to spinal cord injury - Elisa M. Floriddia (Nature Portfolio, 2020)
The oligodendrocyte lineage is known for its transcriptional heterogeneity, but the functional consequences of this are unclear. Here, the authors show that distinct populations of mature oligodendrocytes have spatial preferences in the brain and spinal cord and show different responses to spinal cord injury.